2007
DOI: 10.1096/fj.06-7294com
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia inducible factor regulates the cardiac expression and secretion of apelin

Abstract: Apelin and its G-protein-coupled receptor APJ have various beneficial effects on cardiac function and blood pressure. The mechanisms that regulate apelin gene expression are not known. Because apelin gene expression has been shown to increase in cardiac ischemia, we investigated if apelin (Apln) gene expression was sensitive to hypoxia. Here we show that hypoxia increases the apelin expression in rat myocardium and in cultured cardiomyocytes. Pharmacological activation of hypoxia inducible factor by desferriox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
110
1
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(117 citation statements)
references
References 42 publications
4
110
1
2
Order By: Relevance
“…Endothelial dysfunction is well established in OSA (Atkeson & Jelic 2008) and is ameliorated by CPAP therapy (Jelic et al 2008). Hypoxia-induced myocardial/endothelial apelin expression has been demonstrated via hypoxia-inducible factor (HIF) pathways (Glassford et al 2007, Ronkainen et al 2007, and the HIF-1 pathway is activated in patients with OSA (Atkeson & Jelic 2008). The pulmonary apelin-producing endothelium is particularly sensitive to hypoxia (Sheikh et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial dysfunction is well established in OSA (Atkeson & Jelic 2008) and is ameliorated by CPAP therapy (Jelic et al 2008). Hypoxia-induced myocardial/endothelial apelin expression has been demonstrated via hypoxia-inducible factor (HIF) pathways (Glassford et al 2007, Ronkainen et al 2007, and the HIF-1 pathway is activated in patients with OSA (Atkeson & Jelic 2008). The pulmonary apelin-producing endothelium is particularly sensitive to hypoxia (Sheikh et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Mutagenesis, electrophoretic mobility shift assays and ChIP have also been used in vitro to determine whether upstream stimulatory factors 1 and 2 (USF1 and USF2) are involved in the expression of apelin in the breast, while in vitro ChIP analyses have shown that endogenous USF up-regulates the expression of apelin in the lactating rat breast (Wang et al 2006). Putative hypoxia response elements (HREs) are present in the apelin gene promoter and intron sequence of various species in silico (Cox et al 2006), and hypoxia has subsequently been found to up-regulate the expression of apelin in cardiac myocytes (Ronkainen et al 2007), and hypoxia-inducible factor 1a (HIF1a) has been reported to induce the expression of apelin in adipocytes (Glassford et al 2007). Additional studies have determined that hypoxia-inducible apelin up-regulation is mediated by HIF1a at a HRE within the APLN intron (conserved in rat and mouse apelin genes) between C813 and C826 bp (Eyries et al 2008), indicating that apelin may play a role in the homeostatic response to low oxygen levels.…”
Section: Gene Regulationmentioning
confidence: 99%
“…However, APJ mRNA is decreased in the weakened and enlarged heart of humans with idiopathic dilated cardiomyopathy (Foldes et al 2003). Apelin may have a cardioprotective role in hypoxia and ischaemia, where the cardiac levels of apelin and APJ respectively are increased (Atluri et al 2007, Ronkainen et al 2007, Zeng et al 2009). Apelin may also play a protective a role in ischaemia/reperfusion injury , Zeng et al 2009), although the method of signalling appears to be independent of the characteristic myocardial kinase cascade, termed the reperfusion injury salvage kinase pathway (Kleinz & Baxter 2008).…”
Section: Cardiovascular Roles Of Apelin/apjmentioning
confidence: 99%
“…For this reason it has been suggested as a tool for the treatment of heart failure (HF) [76,70,24,67,77,78]. However, the results of various investigations arise some doubts about this proposal.…”
Section: Inotropic Effectmentioning
confidence: 99%
“…In particular, in the rat the elevation of apelin gene expression in vivo was seen to take place within 24 hours after MI, when an increased apelin release contributes to compensate the sudden HF [76]. Consistently, apelin deficiency in humans worsens the damage of ischemia-reperfusion (I/R), included extension of infarct size, related inflammation and mortality [54].…”
Section: Apelin In Heart Failurementioning
confidence: 99%